Elements of Aristotle’s and Xenocrate’s Philosophies in Alkinoos’s Didaskalikos - Krzakowski, Jerzy Jacek (Folia Philosophica, 2019)
According to Alkinoos, Didaskalikos — being a part of Plato’s doctrine — in fact seems to be a display of a Middle Platonism philosophy. Therefore, it imports a lot from the philosophers of the prior period. This paper deals with the impact of Aristotle’s and Xenocrate’s ideologies on Alkinoos’s interpretation of Plato’s philosophy. It attempts to show that the way Alkinoos classifies philosophies, types of living, the syllogistics and judgement, as well as most of his theology and ethics, is clearly of Aristotelian origins. Also, the terminology adapted by Alkinoos, his interpretation of cosmological terms, epistemology and the issue of God, as well as the theory of idea as a God’s thought, seem to be derived directly from Xenocrate’s concepts. Taking into account the impact of, for example, Antiochus of Ascalon, Philo of Alexandria, Arius Didymus or Posidonius, it seems plausible that Middle Platonism might be a further step in the evolution of philosophical thought.